CLINGING DRAPERY AND CONVERGING COSMOLOGIES: RE-ASSESSING THE NORTHERN QI “QINGZHOU STYLE” - Siyuan HAO; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The 1996 excavation of more than four hundred sixth-century Buddhist sculptures at Longxing-si, Qingzhou, Shandong, profoundly reshaped the study of Northern Dynasties art. A generation of research has illuminated their stylistic hybridity, yet tensions persist between morphological description, laboratory science, and socio-political interpretation. This article reevaluates the so-called “Qingzhou style” of the Northern Qi (550–577 CE) through an integrative approach that links form, materiality, and symbolic function. Based on a first-hand analysis of eighty-seven sculptures, supported by micro-Raman and X-ray fluorescence data, petrographic provenance studies, and donor inscriptional evidence, three key findings are presented. First, the distinctive Cao yi chushui (body-clinging) drapery was not a passive Gupta import nor a purely local innovation but the outcome of state-sponsored standardization that articulated Xianbei cultural legitimacy. Second, petrographic results reveal that most limestone was quarried from Cambrian outcrops within a 20-km radius, indicating tightly controlled networks of production and a sacred geography. Third, iconographic innovations—including robe-carved Huayan cosmograms, hybrid pleat structures, and Sogdian-inspired brocade motifs—mediated transregional vocabularies in ways that challenge linear models of Sinicization or Indianization. By contextualizing stylistic choices within devotional meaning, workshop economies, and imperial power, this article proposes a biocultural-materialist framework for interpreting Buddhist sculpture. The Qingzhou corpus thus emerges not merely as an artistic phenomenon but as cultural infrastructure embodying sixth-century religious piety, ethnic negotiation, and Eurasian artistic exchange.